Cleaning equipment and cleaning system - YAN GUIXIANG; ZHANG YALIN; ZHENG YUE (2024)
The utility model discloses a cleaning device and a cleaning system, the cleaning device comprises a support piece and a detection assembly, the surface of the support piece is provided with a cleaning part, the detection assembly is arranged on the support piece and comprises at least two detection electrodes arranged at intervals, and each detection electrode is respectively contacted with the cleaning part. Therefore, the electrical parameters of the cleaning part can be detected by the detection assembly. In the embodiment provided by the utility model, the control device can control the drying device to work according to the electrical parameters, and the electrical parameters can be electrical signals, such as voltage, current and/or resistance between the at least two detection electrodes, capable of feeding back the dry and wet degree of the cleaning component. In this way, the control device can effectively control the drying duration of the cleaning component according to the dry and wet conditions